HUMAN AND CULTURE - Dwi Putri, Alma Heni; Anggrayni Tanjung, Ricka (International Journal of Students Education, 2023)
Humans and culture are two things that have a close relationship between one another. Humans in this natural world play a unique role, and can be viewed from various aspects, namely in terms of their nature and elements. The purpose of this study is to describe all aspects related to humans and culture in terms of internalization, socialization and enculturation of influences. The method used in this study is a qualitative-descriptive method, using data collection techniques in the form of a review study of books, literature, notes, and reports that have to do with problems solved using secondary data. So the results of the research are processed so that the creation of culture is the result of thoughts, ideas, concepts and beliefs possessed by humans as a gift from God Almighty and beneficial to humans themselves.